Influence of ngeno ngene dialect on english comprehension and pronunciation of students in Tembeng Putik - Azmi, Haerul; Noviana, Ananda Putri (Maliki Interdisciplinary Journal, 2024)
Attempts to master the important English language in this modern era often face difficult challenges, especially from the learner's first language. This study aimed to look at the differences and similarities between the phonemes of the Sasak dialect (Ngeno-Ngene) and English and how they affect the understanding and pronunciation of English. This study used a qualitative approach with library research and observation methods on 8 participants from elementary, junior high, high school, and university levels who read a word list provided by the researcher. Lado's theory of contrastive analysis was used for data analysis. The results showed that there are many similarities and fewer phoneme differences between the Sasak language Ngeno-Ngene dialect and English. In addition, it was revealed that the similarities between the two languages help to pronounce the phonemes correctly, while the differences between the two languages provide phoneme pronunciation challenges, especially on the diphthong phoneme /əʊ/. The findings of this study also showed that the level of learning English positively contributes to the understanding and correct pronunciation of language phonemes. Thus, teachers in primary-level education need to put more effort into teaching English pronunciation given the predicted difficulties that learners may face.